Correlation between plasmid content and infectivity in Borrelia burgdorferi - Purser, Joye E. (The National Academy of Sciences, 2000)
Infectivity-associated plasmids were identified in Borrelia burgdorferi B31 by using PCR to detect each of the plasmids in a panel of 19 clonal isolates. The clones exhibited high-, low-, and intermediate-infectivity phenotypes based on their frequency of isolation from needle-inoculated C3H/HeN mice. Presence or absence of 21 of the 22 plasmids was determined in each of the clones by using PCR primers specific for regions unique to each plasmid, as identified in the recently available genome sequence. Southern blot hybridization results were used to confirm the PCR results in some cases. Plasmid lp25 exhibited a direct correlation with infectivity in that it was consistently present in all clones of high or intermediate infectivity and was absent in all low-infectivity clones. lp28–1, containing the vmp-like sequence locus, also correlated with infectivity; all clones that lacked lp28–1 but contained lp25 had an intermediate infectivity phenotype, in which infection was primarily restricted to the joints. Plasmids cp9, cp32–3, lp21, lp28–2, lp28–4, and lp56 apparently are not required for infection in this model, because clones lacking these plasmids exhibited a high-infectivity phenotype. Plasmids cp26, cp32–1, cp32–2 and/or cp32–7, cp32–4, cp32–6, cp32–8, cp32–9, lp17, lp28–3, lp36, lp38, and lp54 were consistently present in all clones examined. On the basis of these results, lp25 and lp28–1 appear to encode virulence factors important in the pathogenesis of B. burgdorferi B31.